ASSESSMENT OF THE ANTIMICROBIAL ACTIVITY OF Eucalyptus camaldulensis PLANT EXTRACTS - I. Hussein, Ibrahim; A. Jabir, Hamza; A. Gurama, Gurama; U. Idris., Saadatu (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
The eucalyptus camaldulensis plant is extensively used in traditional medicines for treating many diseases. This has prompted the aim of this study to investigate the in vitro antimicrobial activity of the plant to validate its local usage. The leaves and stem barks of E. camaldulensis were subjected to ethanolic extraction via the maceration technique. Standard methods were adopted for the screening of various bioactive phytochemical constituents of the extracts of E. camaldulensis. Varied concentrations between 20 to 100 mg/mL were applied for the antimicrobial susceptibility test against purified microbial isolates (S. aureus, Salmonella typhi, P. aeruginosa, and C. albicans) via the agar wells technique. Lower standards of range 1.56 to 25 mg/mL were adopted for the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) determination. Findings from this study revealed high antimicrobial activity, particularly against bacterial test organisms. The lowest extract concentration (20 mg/mL) produced an 18 mm zone of inhibition against the bacterial test organism while 40 mm was the highest produced at 100 mg/mL. The lowest MIC detected at 6.25 mg/mL further accentuated the inhibitory capability of the E. camaldulensis plant extracts against the test organisms, though no variation in MIC activity between the leaf and stem bark extracts. This research supported the antimicrobial potency of E. camaldulensis extracts which was attributed to its rich sources of phytochemicals.